Strategi Pengembangan Daya Tarik Wisata Bukit Gundaling Di Kabupaten Karo - Ruth Purnama Natalie Ginting; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
Gundaling Hill is a tourist attraction located in the city of Berastagi Karo. The Hill is known as natural tourist attraction since the Dutch colonial era, and has a unique history that makes it more attractive for tourist who visit it. However, Gundaling Hill is no longer attractive for tourist. It is because there is no development on it, and there are some new tourist attractions are established which have replaced the position of Gundaling Hill as a famous tourist attraction in Karo. The research purposes are; to determine the potential of the tourist attraction Gundaling Hill and to determine what needs to be done for the development of Gundaling Hill. This study uses qualitative research methods and the concept of tourism potential and tourism development. Over time Gundaling Hill no longer as beautiful and as well-known as earlier, it is because there is no development is done to the charms of this site, so that tourist no longer feel that Gundaling Hill is a wonderful tourist attraction. The reason are the lack of tourist attractions that are offered, poorly managed, the lack of parking spaces, and the lack of development. It is clear that the role of stakeholders is needed, both from the local community, government and the private sector in oder to develop an attractive tourist attraction in Gundaling Hill. Keywords: Development of Tourist Attractions, Tourism Potential, Tourist Attraction.